2022
DOI: 10.1021/acsomega.2c06662
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical and Pharmacological Evaluation of Amoxicillin after Solubility Enhancement Using the Spray Drying Technique

Abstract: The dose frequency of drugs belonging to class II is usually high and associated with harmful effects on the body. The study aimed to enhance the solubility of the poorly water-soluble drug amoxicillin (AM) by the solid dispersion (SD) technique. Six different SDs of AM, F1−F6, were prepared by the spray drying technique using two other carriers, HP-β-CD (F1−F3) and HPMC (F4−F6), in 1:1, 1:2, and 1:3 drug-to-polymer ratios. These SDs were analyzed to determine their practical yield, drug content, and aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Another study on amoxicillin reported solubility enhancement using spray drying to formulate solid dispersion and fnally achieved sustain release up to 24 h using HPMC and fast release within 60 min using HP-β-CD [23].…”
Section: Statistical Optimization Of Design Batches Tablementioning
confidence: 99%
“…Another study on amoxicillin reported solubility enhancement using spray drying to formulate solid dispersion and fnally achieved sustain release up to 24 h using HPMC and fast release within 60 min using HP-β-CD [23].…”
Section: Statistical Optimization Of Design Batches Tablementioning
confidence: 99%